Численное моделирование рабочего цикла дизеля с непосредственным впрыском. Прогнозирование эмиссии сажи и оксидов азота - Левтеров, Антон Михайлович; Левтерова, Людмила Ивановна (НТУ "ХПИ", 2013)
This article discusses the construction of a mathematical model of the operating cycle of diesel engine with direct injection. This paper also provides that result of modeling becomes possible predict the performance of diesel engine on traditional and alternative fuels with the emission of harmful substances in the exhaust gases, including carbon black, which is particularly important for this type of piston engines.
Keywords: процесс рабочий; углеводороды полициклические; углеводороды ароматические; ацетилен; радикалы; двигатели поршневые